Analysis of the Cash Receipts Accounting Information System in Improving the Internal Control System at PT. BPR Supra Artapersada KPO - Bella Cahya Pertiwi; Venita Sofiani; Evi Martasela (Utan Kayu Publishing, 2024)
Every company must have a cash receipt system and internal controls within it. Therefore, companies must be able to manage this system to avoid potential embezzlement or fraud in the company's cash receipts. An adequate accounting information system and quality internal controls are very important for monitoring cash receipts. The aim of this author is to determine the application of the cash receipts accounting information system in improving internal control at PT. BPR Supra Artapersada KPO. The type of research used by the author uses a qualitative descriptive method, data processed from interviews, observation and documentation. The data was analyzed qualitatively and described in descriptive form. Cash receipt accounting information system at PT BPR. Supra Artapersada KPO has been running well using the Supra Banking System (SBS) application. This system has been computerized and helps the company manage, record and process cash receipt transactions appropriately and supports improving internal control. PT. BPR Supra Artapersada KPO must further improve or update its application system so that all employees who are not assigned to them cannot see cash receipts data. PT. BPR Supra Artapersada KPO also needs to evaluate and improve its organizational structure. Companies must ensure that each position has a clear job description and matches the employee's abilities. To overcome the problem of double jobs, companies should carry out workload analysis and add new human resources if necessary. This will help reduce the risk of performance degradation and increase operational efficiency.